Four Derivative Spectrophotometric Methods for the Simultaneous Determination of Carmoisine and Ponceau 4R in Drinks and Comparison with High Performance Liquid Chromatography - Turak, Fatma; Dinc, Mithat; Dulger, Oznur; Ozgur, Mahmure Ustun (HINDAWI LTD, 2014)
Four simple, rapid, and accurate spectrophotometric methods were developed for the simultaneous determination of two food colorants, Carmoisine (E122) and Ponceau 4R (E124), in their binary mixtures and soft drinks. The first method is based on recording the first derivative curves and determining each component using the zero-crossing technique. The second method uses the first derivative of ratio spectra. The ratio spectra are obtained by dividing the absorption spectra of the binary mixture by that of one of the components. The third method, derivative differential procedure, is based on the measurement of difference absorptivities derivatized in first order of solution of drink samples in 0,1N NaOH relative to that of an equimolar solution in 0,1N HCl at wavelengths of 366 and 451 nm for Carmoisine and Ponceau 4R, respectively. The last method, based on the compensation method is presented for derivative spectrophotometric determination of E122 and E124 mixtures with overlapping spectra. By using ratios of the derivative maxima, the exact compensation of either component in the mixture can be achieved, followed by its determination. These proposed methods have been successfully applied to the binary mixtures and soft drinks and the results were statistically compared with the reference HPLC method (NMKL 130).
Keywords: FOOD COLORS; SYNTHETIC DYES; SOFT DRINKS; MIXTURES; Chemistry